EHF suppresses cancer progression by inhibiting ETS1-mediated ZEB expression - Kaname Sakamoto; Kaori Endo; Kei Sakamoto; Kou Kayamori; Shogo Ehata; Jiro Ichikawa; Takashi Ando; Ryosuke Nakamura; Yujiro Kimura; Kunio Yoshizawa; Keisuke Masuyama; Tomoyuki Kawataki; et al. (Oncogenesis, 2021)
Abstract ETS homologous factor (EHF) belongs to the epithelium-specific subfamily of the E26 transformation-specific (ETS) transcription factor family. Currently, little is known about EHF’s function in cancer. We previously reported that ETS1 induces expression of the ZEB family proteins ZEB1/δEF1 and ZEB2/SIP1, which are key regulators of the epithelial–mesenchymal transition (EMT), by activating the ZEB1 promoters. We have found that EHF gene produces two transcript variants, namely a long form variant that includes exon 1 (EHF-LF) and a short form variant that excludes exon 1 (EHF-SF). Only EHF-SF abrogates ETS1-mediated activation of the ZEB1 promoter by promoting degradation of ETS1 proteins, thereby inhibiting the EMT phenotypes of cancer cells. Most importantly, we identified a novel point mutation within the conserved ETS domain of EHF, and found that EHF mutations abolish its original function while causing the EHF protein to act as a potential dominant negative, thereby enhancing metastasis in vivo. Therefore, we suggest that EHF acts as an anti-EMT factor by inhibiting the expression of ZEBs, and that EHF mutations exacerbate cancer progression.